PERBANDINGAN KADAR PROTEIN SUSU CAIR UHT FULL CREAM PADA PENYIMPANAN SUHU KAMAR DAN SUHU LEMARI PENDINGIN DENGAN VARIASI LAMA PENYIMPANAN DENGAN METODE KJELDHAL - Robby Candra Purnama; Agustina Retnaningsih; Indah Aprianti (Jurnal Analis Farmasi, 2019)
COMPARISON OF THE PROTEIN CONTENT OF UHT FULL CREAM LIQUID MILK AT ROOM TEMPERATURE STORAGE AND REFRIGERATOR TEMPERATUREWITH VARIATIONS IN STORAGE TIME BY THEKJELDHAL METHOD This study aims to determine whether or not there is a decrease in the protein content of full cream liquid milk stored at room temperature and refrigerator temperature analyzed by the Kjeldahl method. The basic principle of Kjeldahl is the calculation of protein content by calculating the element N (nitrogen) based on the sample. From the results of the study the protein content of full cream liquid milk stored at room temperature in sample A from day 0 (2.43%),day 2nd (2.39%), day 4th (2.34%) , day 6th (2.34%), day 8th (2.34%), day 10th (2.32%) and day 12th (2.31%). Whereas in sample B from day 0 (2.41%), day 2nd (2.39%), day 4th (2.34%), day 6th (2.33%), day 8th (2.33%), 10th day (2.32%) and 12th day (2.32%). And the results of determining the protein content of full cream liquid milk stored at the refrigerator temperature in sample A from day 2nd (2.38%), day 4th (2.38%), day 6th (2.38 %), day 8th (2.37%), day 10th (2.36%) and day 12th (2.34%). Whereas in sample B from day 2nd (2.38%), day 4th (2.37%), day 6th (2.36%), day 8th (2.36%), day 10th (2.35%) and day 12th (2.33%). It was concluded that the decrease in protein levels was due to the temperature at the storage time.Keywords: Milk, Protein, Temperature, Kjeldahl Method Penelitian ini bertujuan untuk mengetahui ada atau tidaknya penurunan kadar protein susu cair full cream yang disimpan pada suhu kamar dan suhu lemari pendingin yang dianalisis dengan metode Kjeldahl. Prinsip dasar Kjeldahl adalah perhitungan kadar protein dengan menghitung unsur N (nitrogen) berdasarkan sampel. Dari hasil penelitian kadar protein susu cair full cream yang disimpan pada suhu kamar pada sampel A dari hari ke-0 (2,43%), hari ke-2 (2,39%), hari ke-4 (2,34%), hari ke-6 (2,34%), hai ke-8 (2,34%), hari ke-10 (2,32%) dan hari ke-12 (2,31%). Sedangkan pada sampel B dari hari ke-0 (2,41%), hari ke-2 (2,39%), hari ke-4 (2,34%), hari ke-6 (2,33%), hari ke-8 (2,33%), hari ke-10 (2,32%) dan hari ke-12 (2,32%). Dan pada hasil penetapan kadar protein susu cair full cream yan disimpan pada suhu lemari pendingin pada sampel A dari hari ke-2 (2,38%), hari ke-4 (2,38%), hari ke-6 (2,38%), hari ke-8 (2,37%), hari ke-10 (2,36%) dan hari ke-12 (2,34%). Sedangkan pada sampel B dari hari ke-2 (2,38%), hari ke-4 (2,37%), hari ke-6 (2,36%), hari ke-8 (2,36%), hari ke-10 (2,35%) dan hari ke-12 (2,33%). Disimpulkan penurunan kadar protein tersebut dikarenakan oleh suhu pada lama waktu penyimpanan.Kata kunci: Susu, Protein, Suhu, Metode Kjeldahl